Growth in transition: Selected contributions of the Wuppertal Institute at the 4th International Conference on Degrowth for Ecological Sustainability and Social Equity - Vera Freyling; Philipp Schepelmann; Johannes Buhl; Adelheid Biesecker; Uta von Winterfeld; Benjamin Best (Wuppertal Institut für Klima, Umwelt, Energie, 2015)
In early September 2014, about 4.000 scientists, activists and artists at the 4th International Conference on Degrowth sent out two messages. 1. Industrialized societies will change, either by disaster or by design. Accelerated resource exploitation and climate change can force societies into a transition. Or they swiftly develop new forms of economic, political and social organization which respect the planetary boundaries. 2. "Degrowth" has become a new social movement which translates scientific insights into cultural change, political change and social practice. Hence, the conference itself was an experiment on the potentials and limits of share economy, commoning and sufficiency. A team of young scholars and activists from different German research institutes and non-govern- mental organisations prepared the conference. The team of the Wuppertal Institute was partly involved in the preperation of the conference. Scientists from all research groups took part in the conference, presenting and discussing project results. The publication is a collection of contributions of the Wuppertal Institute to the conference and covers pivotal issues of the degrowth-debate: indicator development (Freyling & Schepelmann), working time reduction (Buhl), feminist theory (Biesecker & Winterfeld), and urban transition (Best). – – Anfang September 2014 sendeten circa 4.000 Wissenschaftler(innen), Aktivist(inn)en und Künstler(innen) auf der vierten internationalen Degrowth Konferenz in Leipzig zwei Botschaften aus: 1. Industrialisierte Gesellschaften werden sich verändern, mittels Desaster oder Design. Zunehmende Ressourcenausbeutung und Klimawandel können Gesellschaften zur Transition zwingen. Es sei denn sie entwickeln rasch neue Formen ökonomischer, politischer und sozialer Organisation, die die Grenzen des Planeten berücksichtigen. 2. "Degrowth" ist zu einer neuen sozialen Bewegung geworden, die wissenschaftliche Einsichten in kulturellen Wandel, politischen Wandel und soziale Praxis übersetzt. Die Konferenz selbst war ein Experiment bezüglich der Potenziale und Grenzen von share economy, commoning und Suffizienz. Die Konferenz wurde von jungen Wissenschaftler(inne)n und Aktivist(inn)en diverser deutscher Forschungsinstitute und Nichtregierungsorganisationen gestaltet. Das Team des Wuppertal Instituts hat teilweise an der Konferenzvorbereitung mitgewirkt. Wissenschaftler(innen) aller Forschungsgruppen nahmen an der Konferenz teil, präsentierten und diskutierten Projektergebnisse. Die Publikation ist eine Sammlung der Konferenzbeiträge aus dem Wuppertal Institut, sie umfasst alle Schlüsselthemen der degrowth-Debatte: Entwicklung von Indikatoren (Freyling & Schepelmann), Arbeitszeitverkürzung (Buhl), Feministische Theorie (Biesecker & Winterfeld), und Urbane Transition (Best).
urn:nbn:de:bsz:wup4-opus-58368
Keywords: 330